PENGARUH DAYA TARIK KONTEN, KEAMANAN INFORMASI, DAN KEMUDAHAN PENGGUNAAN TERHADAP MINAT BELI ULANG PADA PENGGUNA SHOPEE - Uljannah, Lina Pina; Santoso, Adi (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
The utilization of the Shopee application among Indonesian online shoppers has surged in popularity, particularly among Generation Z, making it one of the most favored online shopping platforms in the country. This study endeavors to investigate how content attractiveness, information security, and ease of use affect the intention of Shopee app users to repurchase items. The research targets active students enrolled in the Management Department of Muhammadiyah University of Ponorogo from the 2020-2023 cohorts. Non-probability sampling, specifically employing purposive sampling, was utilized for participant selection. Data collection involved the dissemination of online questionnaires via Google Forms shared across various social media platforms, ultimately reaching 90 respondents. The research variables were assessed multiple linear regression analysis was conducted utilizing a five-point Likert scale. SPSS served as the primary analytical approach. The study findings indicate that while information security does not significantly influence repurchase intention among Shopee app users, both content attractiveness and ease of use significantly impact their intention to repurchase items. Kata Kunci: content appeal, information security, ease of use, repurchase intention